IMPLEMENTING INFORMATION TECHNOLOGY TOOLS IN THE CLINICAL MANAGEMENT AND MONITORING OF CHRONIC DISEASE PATIENTS (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This study evaluates the effectiveness of digital health technologies in early detection and ongoing monitoring of patients with chronic non-communicable diseases (NCDs) such as diabetes, cardiovascular pathologies, and bronchial asthma. The aim is to assess how digital tools improve self-control, clinical outcomes, and patient satisfaction.